1990
DOI: 10.1037/0022-0663.82.4.733
|View full text |Cite
|
Sign up to set email alerts
|

Assessing print exposure and orthographic processing skill in children: A quick measure of reading experience.

Abstract: In a study of third-and fourth-grade children it was established that orthographic processing ability can account for variance in word recognition skill after the variance due to phonological processing has been partialed out. This independent orthographic variance was related to performance on a new measure of individual differences in exposure to print, the Title Recognition Test (TRT), that has a very brief administration time. Additionally, some of the orthographic processing variance linked to word recogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
259
1
7

Year Published

1992
1992
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 325 publications
(282 citation statements)
references
References 39 publications
15
259
1
7
Order By: Relevance
“…For example, in previous work, we have demonstrated that, independent of decoding ability, variation in print exposure among adults predicts variation in specific types of orthographic knowledge (Stanovich & West, 1989). Similarly, in a study of children's performance (Cunningham & Stanovich, 1990), we found that after partialing IQ, memory ability, and phonological processing abilities. print exposure accounted for significant variance in orthographic knowledge and word recognition.…”
Section: Methodological Problems In Assessing the Direct Cognitive Comentioning
confidence: 71%
“…For example, in previous work, we have demonstrated that, independent of decoding ability, variation in print exposure among adults predicts variation in specific types of orthographic knowledge (Stanovich & West, 1989). Similarly, in a study of children's performance (Cunningham & Stanovich, 1990), we found that after partialing IQ, memory ability, and phonological processing abilities. print exposure accounted for significant variance in orthographic knowledge and word recognition.…”
Section: Methodological Problems In Assessing the Direct Cognitive Comentioning
confidence: 71%
“…Finally, we assessed only lexical orthographic knowledge in our study. Given that sublexical orthographic knowledge (e.g., word likeness) is also important for reading fluency (Tims, 2013), or that print exposure could be an intermediate variable between orthographic knowledge and word reading (Cunningham & Stanovich, 1990), future studies should examine the profile of poor readers or spellers on these constructs as well.…”
Section: Discussionmentioning
confidence: 99%
“…Later, a similar test, the Title Recognition Test (TRT), using the same logic as the ART and the MRT, was developed as an additional measure of print exposure (Cunningham & Stanovich, 1990). In these tests, participants are given a list of authors, magazines, or book titles intermixed with a set of compelling foils, and are asked to indicate which items they recognize as the names of real authors, magazines, or book titles, respectively.…”
mentioning
confidence: 99%